The Importance of the Enabling Environment for Business and Economic Growth : A 10 Country Comparison of Central Europe and Africa - Bannock, Graham; Gamser, Matthew; Juhlin, Mariell (World Bank, 2012)
Comparison of the measures adopted to improve the environment for private sector development in Central Europe and Sub-Saharan Africa indicates that these measures can make a real difference to economic performance. Policies should be implemented in consultation with the private sector and should be concerned with removing obstacles so that the private sector can help itself rather than with providing financial or business support. Measures taken should include the reduction of barriers to formal sector activity by establishing clear property rights and minimizing the regulatory costs of doing business. Such measures will reduce the size of the informal sector while promoting growth. A strong lead Ministry with a clearly defined role for promoting private sector development is needed.